Molecular Biomarkers of Neovascular Age-Related Macular Degeneration With Incomplete Response to Anti-Vascular Endothelial Growth Factor Treatment - Mantel, Irmela; Borgo, Angelica; Guidotti, Jacopo; Forestier, Edwige; Kirsch, Olga; Derradji, Yasmine; Waridel, Patrice; Burdet, Frédéric; Mehl, Florence; Schweizer, Claude; Roduit, Raphaël (Frontiers in Pharmacology, 2020)
The standard treatment for neovascular age-related macular degeneration (nAMD) consists of intravitreal anti-vascular endothelial growth factors (VEGF). However, for some patients, even maximal anti-VEGF treatment does not entirely suppress exudative activity. The goal of this study was to identify molecular biomarkers in nAMD with incomplete response to anti-VEGF treatment. Aqueous humor (AH) samples were collected from three groups of patients: 18 patients with nAMD responding incompletely to anti-VEGF, 19 patients affected by nAMD with normal treatment response, and 14 control patients without any retinopathy. Proteomic and multiplex analyses were performed on these samples. Proteomic analyses showed that nAMD patients with incomplete anti-VEGF response displayed an increased inflammatory response, complement activation, cytolysis, protein-lipid complex, and vasculature development pathways. Multiplex analyses revealed a significant increase of soluble vascular cell adhesion molecule-1 (sVCAM-1) [p=0.001], interleukin-6 (IL-6) [p=0.009], bioactive interleukin-12 (IL-12p40) [p=0.03], plasminogen activator inhibitor type 1 (PAI-1) [p=0.004], and hepatocyte growth factor (HGF) [p=0.004] levels in incomplete responders in comparison to normal treatment response. Interestingly, The same biomarkers showed a high intercorrelation with r2 values between 0.58 and 0.94. In addition, we confirmed by AlphaLISA the increase of sVCAM-1 [p<0.0001] and IL-6 [p=0.043] in incomplete responder group. Incomplete responders in nAMD are associated with activated angiogenic and inflammatory pathways. The residual exudative activity of nAMD despite maximal anti-VEGF treatment may be related to both angiogenic and inflammatory responses requiring specific adjuvant therapy.